2014
DOI: 10.1021/la404978f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Calipers for Highly Precise and Accurate Measurements of Single-Protein Mechanics

Abstract: Single-molecule atomic force spectroscopy (AFM) has evolved into a powerful technique toward elucidating conformational changes in proteins when exposed to applied force. AFM technologies that are currently available allow for precise measurements of proteins length changes during conformational transitions. However, because of systematic errors in piezo calibration as well as errors originating from fitting experimental data using a worm-like chain model of polymer elasticity, high-precision measurements of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…To investigate the mechanical unfolding mechanism of aFd, we first constructed the Cys-aFd-GL15-Cys heterodimer, and used maleimide–thiol coupling chemistry to construct the polyprotein (aFd-GL15) n for single-molecule AFM experiments . GL15 is a loop insertion variant of the small model protein GB1 in which a stretch of 15 flexible residues is inserted into the second loop of GB1. , The signatures of the mechanical unfolding of GL15 are a contour length increment (Δ L c ) of ∼23 nm and a unfolding force of ∼150 pN at a pulling speed of 400 nm/s, as detailed in our previous work . The well-characterized GL15 domain serves both as a “fingerprint domain” for detecting single-molecule force spectrum for (aFd-GL15) n , as well as an internal force caliper in the (aFd-GL15) n polyprotein .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…To investigate the mechanical unfolding mechanism of aFd, we first constructed the Cys-aFd-GL15-Cys heterodimer, and used maleimide–thiol coupling chemistry to construct the polyprotein (aFd-GL15) n for single-molecule AFM experiments . GL15 is a loop insertion variant of the small model protein GB1 in which a stretch of 15 flexible residues is inserted into the second loop of GB1. , The signatures of the mechanical unfolding of GL15 are a contour length increment (Δ L c ) of ∼23 nm and a unfolding force of ∼150 pN at a pulling speed of 400 nm/s, as detailed in our previous work . The well-characterized GL15 domain serves both as a “fingerprint domain” for detecting single-molecule force spectrum for (aFd-GL15) n , as well as an internal force caliper in the (aFd-GL15) n polyprotein .…”
Section: Resultsmentioning
confidence: 97%
“…GL15 is a loop insertion variant of the small model protein GB1 in which a stretch of 15 flexible residues is inserted into the second loop of GB1. , The signatures of the mechanical unfolding of GL15 are a contour length increment (Δ L c ) of ∼23 nm and a unfolding force of ∼150 pN at a pulling speed of 400 nm/s, as detailed in our previous work . The well-characterized GL15 domain serves both as a “fingerprint domain” for detecting single-molecule force spectrum for (aFd-GL15) n , as well as an internal force caliper in the (aFd-GL15) n polyprotein . Stretching the (aFd-GL15) n polyprotein allowed us to stretch aFd from its N- and C-termini.…”
Section: Resultsmentioning
confidence: 99%
“…18,33 Fitting the sawtooth peaks to the worm-like chain (WLC) model of polymer elasticity clearly revealed two populations of unfolding events: blue events with a contour length increment (DLc) of $18 nm, and events colored in red with a DLc of $28 nm, corresponding to the unfolding of the oxidized reconstituted GL5CC and I27 domains, respectively. 32,33,35 The observed number of unfolding force peaks of GL5CC and I27 domains in a force-extension curve is oen more than 13, indicating that the stretched protein polymer is at least a septamer of (G C -I27-G N ) n . These observations indicated that the stretched protein polymers are indeed continuous protein polymers made of tandem repeats of Representative force-extension curves of the G C -I27-G Nbased protein polymers (200 mM G C -I27-G N was used in the polymerization).…”
Section: Single Molecule Spectroscopy Experiments Conrmed the Naturementioning
confidence: 99%
“…G N and G C are two fragments from GL5CC we constructed previously. 30,32 GL5CC is split into two fragments at residue 42: G N is the N-terminal fragment (residues 1-42) and G C is the Cterminal fragment (residues 43-61). Both G N and G C were amplied with the template of GL5CC-27w34f through polymerase chain reaction (PCR).…”
Section: Protein Engineeringmentioning
confidence: 99%
See 1 more Smart Citation